2001
DOI: 10.1093/ajcn/74.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in dietary intakes, physical activity, and energy expenditure in middle-aged, premenopausal women: the Healthy Transitions Study

Abstract: Background:Menopause is a time of increased risk of obesity in women. The effect of menopause in African American women, in whom obesity is already highly prevalent, is unknown. Objective: We compared dietary intakes and energy expenditure (EE) between middle-aged, premenopausal African American and white women participating in a longitudinal study of the menopausal transition. Design: Dietary intakes by food record, EE by triaxial accelerometer, physical activity by self-report, and body composition by dual-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
1
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(86 citation statements)
references
References 29 publications
5
78
1
2
Order By: Relevance
“…However, these ethnic differences were largely attributed to differences in PAEE, and not as a result of lower REE, as previously reported in studies from the United States (Albu et al, 1997;Foster et al, 1997;Carpenter et al, 1998;Hunter et al, 2000;Weinsier et al, 2000Weinsier et al, , 2002Lovejoy et al, 2001;Sharp et al, 2002). In the present study, total PAEE was on average 25% lower in the black as compared to white women, largely due to between-group differences in the weight-bearing stepping exercise, where white obese women accumulated a significantly greater PAEE (11%) than black women.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, these ethnic differences were largely attributed to differences in PAEE, and not as a result of lower REE, as previously reported in studies from the United States (Albu et al, 1997;Foster et al, 1997;Carpenter et al, 1998;Hunter et al, 2000;Weinsier et al, 2000Weinsier et al, , 2002Lovejoy et al, 2001;Sharp et al, 2002). In the present study, total PAEE was on average 25% lower in the black as compared to white women, largely due to between-group differences in the weight-bearing stepping exercise, where white obese women accumulated a significantly greater PAEE (11%) than black women.…”
Section: Discussionsupporting
confidence: 82%
“…Studies (Albu et al, 1997;Carpenter et al, 1998;Hunter et al, 2000;Lovejoy et al, 2001;Sharp et al, 2002;Weinsier et al, 2002) have reported lower resting energy expenditure (REE) in obese and reduced obese African American (AA) women compared to their white counterparts (Foster et al, 1997;Weinsier et al, 2000). This difference in REE persists even after adjusting for differences in fat-free mass (FFM) (Foster et al, 1999), and is thought to contribute to the higher obesity prevalence found in the AA compared to the white population.…”
Section: Introductionmentioning
confidence: 99%
“…1 Observational studies have shown an inverse relationship between dietary calcium intake (particularly from dairy sources) and body fat/weight, [2][3][4][5][6] although not consistently observed. 7 Similarly, dietary patterns with a high intake of dairy food/calcium have been linked to reduced incidence of insulin resistance in overweight adults, 8 lower blood pressure 9 and improved lipid profile.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of studies demonstrate that higher intakes of calcium or dairy products, the predominant dietary source of calcium in the US, are associated with weight loss, with some showing specificity to fat mass loss. [9][10][11][12][13][14][15][16][17][18][19][20][21] For example, we conducted a secondary analysis of data collected in our laboratory during a 2-year exercise intervention trial in 54 young, healthy women. 16 Results indicated that calcium intake, adjusted for calories, was negatively associated with changes in body weight and fat mass in women whose energy intakes were at or below the overall group mean of 1876 kcal/day.…”
Section: Introductionmentioning
confidence: 99%